2022
DOI: 10.1027/0269-8803/a000280
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Method Approach to Understand Parent Behaviors During Child Acute Pain

Abstract: Abstract. Parent behaviors strongly predict child responses to acute pain; less studied are the factors shaping parent behaviors. Heart rate variability (HRV) is considered a physiological correlate of emotional responding. Resting or “trait” HRV is indicative of the capacity for emotion regulation, while momentary changes or “state” HRV is reflective of current emotion regulatory efforts. This study aimed to examine: (1) parent state HRV as a contributor to parent verbal behaviors before and during child pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
2
3
1
Order By: Relevance
“…Thus, parents who had greater regulation capacity before the procedure engaged in less frequent coping- and distress-promoting behaviors which may suggest these parents felt less threatened by the procedure and therefore less need to engage their child verbally. This aligns with lab-based findings, reporting an inverse association between parent HRV during child pain and rate of coping-promoting behaviors [ 17 ]. There were no moderation effects of parent baseline HRV between child distress and parent behaviors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, parents who had greater regulation capacity before the procedure engaged in less frequent coping- and distress-promoting behaviors which may suggest these parents felt less threatened by the procedure and therefore less need to engage their child verbally. This aligns with lab-based findings, reporting an inverse association between parent HRV during child pain and rate of coping-promoting behaviors [ 17 ]. There were no moderation effects of parent baseline HRV between child distress and parent behaviors.…”
Section: Discussionsupporting
confidence: 87%
“…Catastrophizing, characterized by a focus on and magnification of the threat value of painful stimuli, commonly relates positively to distress-promoting behaviors (e.g., [ 11 ]); however, we show that this association varies based on parent baseline HRV. Parents with low baseline HRV, or low capacity to regulate their emotions, appear to be most vulnerable to engaging in unhelpful verbal behaviors during their child’s venipuncture, particularly if they were experiencing catastrophic thoughts before the procedure, which aligns with lab-based findings [ 17 ]. We extend these findings to a clinical context, controlling for child distress behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, physiological responses to threat are largely products of subcortical circuits underlying defensive responses, which often operate outside of conscious awareness (LeDoux & Pine, 2016). Thus, the lack of significant associations between parent self‐reported states and HRV may speak to the unique information captured by each measure, which is consistent with past lab‐based research (e.g., Constantin et al., 2022; Vervoort et al., 2014, 2019). A stronger association may emerge between parent HRV and behavioral cues, both of which derive in part from automatic and reflexive autonomic systems.…”
Section: Discussionsupporting
confidence: 77%
“…The results indicated a mean rate of 40.08 ( SD = 11.29) in relation to parental distress. This rate is higher than the average rate previously reported for the normative and low distress population (for example, Spielberger et al ( 1983 ), M = 35, SD = 10.5; Constantin et al ( 2022 ), M = 29.09, SD = 19.40), and closer to a study with a clinical population of high-risk women ( M = 44.6, SD = 9.9; Van der Bij et al, 2003 ). Moreover, we found that 63% of the participants reported a higher score than 35, suggesting that around two-thirds of the sample experienced an elevated level of distress during the assessment time.…”
Section: Resultscontrasting
confidence: 60%